Flexural behaviour and design of hollow flange cold-formed steel beam filled with lightweight normal and lightweight high strength concrete - Sifan, Mohamed; Gatheeshgar, Perampalam; Navaratnam, Satheeskumar; Nagaratnam, Brabha; Poologanathan, Keerthan; Thamboo, Julian; Suntharalingam, Thadshajini (Journal of Building Engineering, 2022)
A comprehensive investigation of the flexural behaviour of concrete-infilled hollow flange cold formed steel (CF-HFCFS) beams with lightweight normal and lightweight high strength concrete is presented in this paper. These are new generation of complex members, and their enhanced structural capacity is governed by inter-related parameters including composite action. However, the knowledge surrounding the flexural performance of lightweight concrete infilled hollow flange cold formed steel (HFCFS) beam is limited. This work aims to study the influence of key parameters on flexural behaviour of CF-HFCFS through numerical analysis and is followed by developing a simplified design approach. A non-linear finite element (FE) model of HFCFS beams with and without lightweight concrete infill was developed. The developed FE model was validated against the experimental results available in the literature. The validated model was subsequently used to conduct a parametric study. The parametric study also included the HFCFS beams without concrete infill for comparison purposes. It was found that the concrete infill contributes to up to 55% of flexural capacity enhancement compared to the bare HFCFS beams. The suitability of the existing design approach available in the literature for the concrete infilled structural steel tubes under flexure was assessed and modifications are proposed. In addition, using the numerically derived data, a novel simplified design approach was developed based on the capacity improvement factor method to estimate the moment capacity. The developed equations have shown to be accurate in estimating the moment capacity of concrete infilled hollow flange beams. •The flexural behaviour of HFCFS beams with and without lightweight concrete infill has been investigated.•Parametric studies have been conducted by considering the influential parameters.•Flexural capacity increments up to 55% were observed with concrete infilled in CF-HFCFS beams.•New simple design equations were proposed, and they give very satisfactory results.